1998
DOI: 10.1159/000006859
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Cardiac Troponin I and Creatine Kinase-MB Isoenzyme in Asymptomatic Long-Term Hemodialysis Patients and Effect of Hemodialysis on These Cardiac Markers

Abstract: Objectives: The objectives of this study were: (1) to evaluate the specificity of cardiac troponin I and creatine kinase-MB isoenzyme in ambulatory asymptomatic chronic renal failure patients on long-term hemodialysis, and (2) to evaluate the effect of hemodialysis on the serum levels of cardiac troponin I and creatine kinase-MB isoenzyme. Methods: One hundred and forty-four consecutive ambulatory asymptomatic chronic renal failure patients on hemodialysis for a minimum of 1 year were evaluated clinically. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Regarding intradialytic variations, the results of our study indicate, accordingly to the results of previous studies [8,20,21], that HD procedure does not significantly affect cTnI blood concentrations by itself. In our patients, no significant changes were observed between pre- and post-HD cTnI levels both considering separately the 3 HD weekly sessions and both considering the average values (Table 3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding intradialytic variations, the results of our study indicate, accordingly to the results of previous studies [8,20,21], that HD procedure does not significantly affect cTnI blood concentrations by itself. In our patients, no significant changes were observed between pre- and post-HD cTnI levels both considering separately the 3 HD weekly sessions and both considering the average values (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, previous studies showed conflicting results regarding HD effects on cTnI levels, with some reporting no changes [8,20,21], others a decrease [11,22,23], and others an increase in cTnI values after HD [10,24]. The aim of this study was to investigate the effect of single and several HD treatments on cTnI levels in ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…127,128 Atherosclerotic risk factors such as diabetes, 129,130 hypercholesterolemia, 131,132 left ventricular hypertrophy 133,134 and severe coronary artery calcification 135 are associated with increases in cTnT levels in hemodialysis patients, which supports the concept that elevations are secondary to myocardial injury. 136,137 In a study by Ooi and colleagues, 138 minor elevations in troponin levels were invariably associated with pathological evidence of myocardial damage in patients with and without renal failure. Furthermore, prognostic studies have confirmed that such elevations are indicators of future cardiac events.…”
Section: Troponin and Renal Failurementioning
confidence: 99%
“…Most previous studies of cardiac biomarkers in ESRD present conflicting results [15][16][17][18][19]. Postdialysis values increased, decreased or remained stable compared to predialysis concentrations.…”
Section: Discussionmentioning
confidence: 93%